THE LEVEL OF COMPLIANCE BEHAVIOR IN USING PERSONAL PROTECTIVE EQUIPMENT ON NURSE IN THE HOSPITAL - Lina Yuliana (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2018)
Healthcare Associated Infections (HAIs) is one of the risks for nurses in the hospital. Several diseases related to the HAIs, such as HIV and hepatitis. The level of compliance behavior in using PPE is one of the solutions in controlling the hazards caused by illnesses and injuries (accident). Hospital X is one of the general hospitals in Surabaya. Accident rates for patient's body fluids and needle stick injury are 51.1% and 46.7%.Aims: This study was aimed to analyze the correlated factor with the  level of   compliance behavior in using personal protective equipment (PPE) on nurses at inpatient installation. Methodology and results: This research was a quantitative method with cross sectional design and observational study. The total sample technique was used to get sample (n = 29). The result of this study is the correlation coefficient of employment status (r = 0.340), working shift (r = 0.446), knowledge (r= 0,394), Attitude (r= 0,215 ). From the result of correlation test, that is shown the work shift is stronger correlation than knowledge with the level of compliance behavior. From the result of regression test simultanly, that is showing the variables of working shift and knowledge were significant values. Then, the value of Pseudo R-Square, the variables of working shift andd knowledge is about 46,9%.. Conclusion: Work shift and knowledge have a correlation to the level of compliance behavior in using PPE, both in bivariate and multivariate test.